2013
DOI: 10.1002/pros.22665
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming and Validation of Hyperpolarized13C Lactate as a Prostate Cancer Biomarker Using a Human Prostate Tissue Slice Culture Bioreactor

Abstract: BACKGROUND The treatment of prostate cancer has been impeded by the lack of both clinically relevant disease models and metabolic markers that track tumor progression. Hyperpolarized (HP) 13C MR spectroscopy has emerged as a new technology to investigate the metabolic shifts in prostate cancer. In this study, we investigate the glucose reprogramming using HP 13C pyruvate MR in a patient-derived prostate tissue slice culture (TSC) model. METHODS The steady-state metabolite concentrations in freshly excised hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
122
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(138 citation statements)
references
References 57 publications
13
122
3
Order By: Relevance
“…The [1- 13 C]lactate signal was low or undetectable in slices from regions of the prostate that did not include tumor. This agrees with previous patient prostate biopsy studies, which demonstrated very low lactate concentrations (30), and with preclinical studies, which demonstrated a low flux of hyperpolarized [1- 13 C]pyruvate to lactate in normal prostate (17). The 2D dynamic MRSI data were able to distinguish signals from tumor and vessels, with the rate of [1- 13 C]pyruvate to [1- 13 C]lactate conversion being four to five times higher in tumor.…”
Section: Discussionsupporting
confidence: 91%
“…The [1- 13 C]lactate signal was low or undetectable in slices from regions of the prostate that did not include tumor. This agrees with previous patient prostate biopsy studies, which demonstrated very low lactate concentrations (30), and with preclinical studies, which demonstrated a low flux of hyperpolarized [1- 13 C]pyruvate to lactate in normal prostate (17). The 2D dynamic MRSI data were able to distinguish signals from tumor and vessels, with the rate of [1- 13 C]pyruvate to [1- 13 C]lactate conversion being four to five times higher in tumor.…”
Section: Discussionsupporting
confidence: 91%
“…Consistently, lactate dehydrogenase B, which catalyzes the lactate to pyruvate conversion, is suppressed [131,134]. This is further functionally supported by experiments with hyperpolarized pyruvate, where in situ tumors convert pyruvate into lactate [135][136][137]. Thus, it is questionable whether cells in vivo exchange lactate or rather other substrates (e.g.…”
Section: Early Stage Prostate Cancer Metabolismmentioning
confidence: 94%
“…re lease large amounts of lac tate in vivo [259][260][261]. Al though stud ies on cell cul tures showed that mi to chon dr ial res pi ra tion is lim ited in sev eral can cer cell lines [262][263][264], in vivo data showed that mi to chon dr ial oxy gen con sump tion is not im paired in tu mors and that ox ida tive glu cose me tab o lism is re quired for tu mor growth [265].…”
Section: Metabolic Differences Between In Vitro and In Vivo Models Ofmentioning
confidence: 99%